The concept of the human being in the Xunzi - Li, Jifen (2015)
The moral necessity of ritual propriety is grounded on Xunzi’s argument that the original state of human nature is bad and people need to depart from it. For Xunzi, ritual propriety is the foundation for achieving humanity. Furthermore, ritual propriety is not merely an instrument for human beings, but also is fused with the existence of human beings. In the horizon of ritual propriety, the human being for Xunzi is a constructive and relational human being. To illustrate this, I turn to Xunzi’s emphasis of simu 思慕, or appreciative mourning, which for Xunzi is an important component of self-cultivation. Finally, Xunzi’s argument on the guardian role of human beings shows humans’ loving care of other creatures in nature. It is from this loving care, I argue, that an idea of being friendly with nature can be developed from Xunzi.